More than maps: Providing an alternative for fisheries and fishers in marine spatial planning. (1st May 2019) - Trouillet, Brice; Bellanger-Husi, Lise; El Ghaziri, Angélina; Lamberts, Christine; Plissonneau, Elodie; Rollo, Nicolas
Abstract: Although a necessary approach in many cases, implementing Marine Spatial Planning (MSP) reveals discrepancies between theory and practice. These discrepancies include the major importance given to technical issues along with the role and meaning ascribed to the "spatial" dimension at the expense of the "strategic" one. This gives rise to questions especially from the point of view of fisheries that invite to develop a more in-depth critical analysis of MSP. Far from considering the technical and political dimensions in opposition, the goal is to find out whether the reasoning used can be turned around, or in other words, whether the potential of a mapping instrument can be used to give greater importance and more visibility to strategic questions in MSP processes. Our reflection is based on methods used to map fisheries. It is also enhanced by notions such as empowerment and asserting the value of non-scientific knowledge in-situ. To test the strengths and shortcomings of this idea, it was applied in the context of an ongoing 2010 experiment between scientists (geographers and statisticians), fishers and fishers' representatives in metropolitan France. They have been working together for several years and have gradually expanded their scope to now include almost three-quarters of French metropolitan fleets (around 3250 vessels). This experiment shows that fishers and their representatives are not only able to generate spatial data using robust methods (almost 6000 surveys have already been conducted), but more importantly that they are also able to draw on this knowledge and participate in debates in a more effective manner, taking on the role of "real actors". This has enabled a more political alternative to take shape, full of promise and giving rise to new questions. Highlights: A summary of methods used to map fisheries was established. A method that enables fishers to assert their knowledge themselves was developed. Data (6000 surveys) on fishing areas was collected using this method. This data allowed fishers to participate in the discussions concerning sharing maritime space. This experiment proved the existence of possible alternatives for rethinking MSP.